Model Kurikulum Integratif Pesantren Mahasiswa dan UIN Maliki Malang - Husniyatus Salamah Zainiyati (Ulumuna, 2014)
Some PTAINs develop a Ma’had in their campuss. This article is aimed at analyzing the integration of curiculum of UIN Maliki into those of its Ma’had which is called correlated curriculum model. Following this model, students of the Ma’had have to take several steps to complete their study. They have to obtain a certificate of completion of ta‘līm al-afkar al-Islāmī and ta‘lim al-Qur’ān which is required for enrolling in the Islamic studies program and taking comprehensive exam. The Ma’had applies Qur’anic-based learning system. This system maps the concept of science and the religious knowledge, integrates the concept of science and theose of the religious knowledge and elaborates the Qur’anic verses scientifically. The ma’had maintains the tradition of congregational pray, recitation and memorization of the Qur’an and promotes infaq and ṣadaqah. All these are to develop the Islamic culture among the academic community at UIN Malang.